2021
DOI: 10.1096/fj.202100282r
|View full text |Cite
|
Sign up to set email alerts
|

The fibrillin‐1 RGD motif posttranscriptionally regulates ERK1/2 signaling and fibroblast proliferation via miR‐1208

Abstract: Fibrillin-1 is an extracellular matrix protein which contains one conserved RGD integrin-binding motif. It constitutes the backbone of microfibrils in many tissues, and mutations in fibrillin-1 cause various connective tissue disorders. Although it is well established that fibrillin-1 interacts with several RGD-dependent integrins, very little is known about the associated intracellular signaling pathways. Recent published evidence identified a subset of miRNAs regulated by fibrillin-1 RGD-cell adhesion, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The FBN1 gene encodes a fibrillin-1 protein, a multidomain extracellular glycoprotein that plays an essential role in maintaining the function and integrity of connective tissues [61,62]. Increased expression of fibrillin-1 has been associated with the development of fibrosis in organs such as the skin, liver, and kidneys [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FBN1 gene encodes a fibrillin-1 protein, a multidomain extracellular glycoprotein that plays an essential role in maintaining the function and integrity of connective tissues [61,62]. Increased expression of fibrillin-1 has been associated with the development of fibrosis in organs such as the skin, liver, and kidneys [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of fibrillin-1 has been associated with the development of fibrosis in organs such as the skin, liver, and kidneys [63][64][65]. It has been described that fibrillin-1 can interact directly with cell surface transmembrane receptors such as integrins and thus favor fibroblast proliferation [62]. On the other hand, recent studies have reported that microfibrils isolated from the skin of Tsk−/− mice, a model of systemic sclerosis, maintain a statistically significant increase in fibrillin-1 and are associated with the upregulation of a prooxidant phenotype in endothelial cells, thus facilitating their activation and mesenchymal transition [63].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, MFS is caused by mutations in the FBN1 gene. Some studies reported that FBN1 –cell interaction regulates a group of miRNAs in an “outside-in” manner, influencing cell proliferation, focal adhesion and TGF-β signaling [ 105 , 106 ]. In this light, Zhang et al investigated the role of fibrillin-1-controlled miRNA in the regulation of inflammatory responses and MMP12 expression in MFS pathogenesis [ 107 ].…”
Section: Mirna Regulation Of Vascular Cell Phenotype In Genetic Taasmentioning
confidence: 99%
“…Furthermore, the RGD motif of FBN1 inhibits the expression of miR-1208 via c-Src kinase and its downstream JNK signaling. The suppression of miR-1208 leads to elevated levels of both total and phosphorylated ERK1/2 and MEK1/2 proteins, together with an increase in the ratio of phosphorylated to total ERK1/2 ( Zhang et al, 2021 ).…”
Section: Fbn1 and Other Signaling Pathwaymentioning
confidence: 99%